Converting to inclusive online flipped classrooms in response to Covid-19 lockdown - Gerber, A.; Eybers, S. (South African Journal of Higher Education, 2021)
The global Covid-19 pandemic caused havoc in higher education teaching routines and several residential institutions encouraged instructors to convert existing modules to flipped classrooms as part of an online, blended learning strategy. Even though this seems a reasonable request, instructors straightaway encountered challenges which include a vague concept of what an online flipped classroom entails within a higher education context, a lack of guidelines for converting an existing module, facilitating learner engagement as well as unique challenges for inclusion of all learners in a digitally divided developing country in Covid-19 lockdown. In order to respond, we embarked on a study to identify the distinguishing characteristics of flipped classrooms to understand the as-is and to-be scenarios using a systematic literature review. The characteristics were used to develop of design considerations to convert to an online flipped classroom for higher education taking our diverse learner profiles into account. We subsequently converted a short module in an information systems department and shortly report on our experience.